Komparace zdaňování příjmů fyzických osob v České republice a na Slovensku - Heinzová, Lenka (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Bakalářská práce na téma “Komparace zdanění fyzických osob v České republice a na Slovensku“ se zaměřuje na problematiku zdanění příjmů fyzických osob v České republice a na Slovensku, dle zákonů platných v roce 2017. V teoretické části práce jsou popsány základní pojmy, daňový systém v daných zemích a postup zdanění příjmů fyzických osob. Praktickou část práce tvoří konkrétní příklady zdanění těchto dvou států (fiktivní) a dále návrhy na optimalizaci daní v České republice.

The bachelor thesis "Comparison of Taxation of Individuals in the Czech Republic and Slovakia" focuses on the issue of taxation of income of individuals in the Czech Republic and Slovakia, according to the laws in force in 2017. In the theoretical part of the thesis are described the basic concepts, the tax system in this countries and the procedure for taxing the income of natural persons. The practical part of the thesis is a concrete example of taxation of these two states (fictitious) and proposals for optimization of taxes in the Czech Republic.
Comparison of Personal Income tax in the Czech Republic and the Slovakia
Keywords: Česká republika; Slovensko; daň; fyzická osoba; poplatník; komparace; příjem; Czech Republic; Slovakia; tax; natural person; taxpayer; comparison; income